Benign prostate hyperplasia and prostate cancer differentiation calculator - M. I. Kogan; M. E. Efremov; V. L. Medvedev; T. G. Sinyavskaya (Вестник урологии, 2025)
Introduction. Differential diagnosis of benign prostate hyperplasia (BPH) and prostate cancer (PCa) is a complex, multi-stage process. It is known that men with BPH and PCa have significant differences in their sexual activity throughout life.Objective. To devise a model for predicting the risks of developing PCa or BPH, considering male sexual activity, and to construct a calculator based on this model to distinguish between the two conditions.Materials & methods. An open prospective non-comparative сross-section study involved 47 men aged 49–71 years with BPH and 87 men aged 47 – 70 years who had been newly diagnosed with PCa. The patients underwent testing for serum PSA levels, total testosterone, and prostate volume. The results of the survey based on the “Rostov Integral Assessment of Male SExuality Questionnaire — RIAMSE” were evaluated.Results. Logistic regression techniques have shown that a patient's sexuality, prostate volume, and PSA level can be predictive of a patient's risk of having either a BPH or an PCa. A 1-point increase in sexuality increases the odds that a patient will be diagnosed with BPH rather than PCa by an average of 1.08 times. If the volume of the PSA increases by 1 cm3, the odds of being diagnosed with BPH increase by an average of 1.15 times. A 1 ng/ml increase in PSA level decreases the odds of detecting BPH compared to PCa by a factor of 0.13. A differentiation calculator was developed based on the results of mathematical modelling.Conclusion. The simple calculator presented in the study has a sensitivity and specificity > 0.90 and can be evaluated in upcoming clinical trials.